Cancer in the lives of older Americans : blessings and battles - Kagan, Sarah H. (Sarah Hope) (EBL-Schweitzer, 2009)
Little has been written to guide clinicians, social scientists, families, and individuals about cancer among the "oldest old." In Cancer in the Lives of Older Americans, Sarah H. Kagan approaches this problem from the perspective of more than twenty years of practice, inquiry, and education as a nurse.